A Pyrene‐Triazacyclononane Anchor Affords High Operational Stability for CO2RR by a CNT‐Supported Histidine‐Tagged CODH. (23rd March 2022) - Contaldo, Umberto; Curtil, Mathieu; Pérard, Julien; Cavazza, Christine; Le Goff, Alan
Abstract: An original 1‐acetato‐4‐(1‐pyrenyl)‐1, 4, 7‐triazacyclononane (AcPyTACN) was synthesized for the immobilization of a His‐tagged recombinant CODH from Rhodospirillum rubrum ( Rr CODH) on carbon‐nanotube electrodes. The strong binding of the enzyme at the Ni‐AcPyTACN complex affords a high current density of 4.9 mA cm −2 towards electroenzymatic CO2 reduction and a high stability of more than 6×10 6 TON when integrated on a gas‐diffusion bioelectrode. Abstract : A pyrene‐triazacyclononane‐Ni carbon‐nanotube anchor affords million‐turnover stability for an electroenzymatic CO2 ‐to‐CO reduction reaction by a recombinant carbon monoxide dehydrogenase.